EKSEKUSI PUTUSAN PENGADILAN TENTANG HAK ASUH ANAK - Mubarok, Muhammad Fikri; Arimbi, Diah; Wati, Endang Eko (Economics, Social, and Humanities Journal (Esochum), 2024)
Child custody disputes resulting from divorce are the problem in this case. The struggle for custody of minors is the subject of dispute in the implementation between the decision and the implementation of the decision which is difficult to implement where the decision explains that the custody of the child falls to the mother but in reality, the child is still in the care of his father. This basis is of research interest so the purpose of this research is to find out the implementation or execution of the Purwokerto Court Decision Number 1857/Pdt.G/2017/PA.Pwt jo Semarang Religious High Court Decision Number 170/Pdt.G/2018/PTA.Smg jo Supreme Court RI Decision Number 57/K/Ag/2019 regarding child custody and knowing the legal protection of children after court decisions. The research method used was normative juridical and limited empirical juridical. Based on the results of the research, showed that there was no system for executing decisions related to child custody, so the Defendant requested assistance from the local village head, security represented by Babinsa, police, Women and Children Services Unit (PPA), but the Plaintiff was offered various options but the process is long. Therefore, in addition to the court decision determining that custody was to be given to Plaintiff, the transfer of care was made because the child did not feel comfortable with Defendant and was willing to live with Plaintiff as his biological mother, which facilitated the process of transferring control of the child. The legal protection given to the child after the divorce of his parents was that the child still got maintenance from his parents, especially from his father, if the child born in the family was a girl then his biological father remains the guardian of the marriage, the relationship between parents and children was valid forever even though there was a divorce the child still gets inheritance from his parents.